2010
DOI: 10.1002/ejoc.200901468
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies of a One‐Flask Synthesis of 3H‐1‐Benzazepines from 2‐Haloanilines and α,β‐Unsaturated Ketones

Abstract: Abstract3H‐1‐Benzazepines are prepared in one step from the reaction of 2‐fluoro‐ or 2‐chloroaniline and several aryl vinyl ketones. Enones 9a–c gave benzazepines 11a–c as expected, showing that alkyl substitution at C4 and C5 in the benzazepines is possible. However, enone 9d underwent decomposition due to conjugate addition of the 2‐fluoroaniline, while enone 10 gave unsaturated imine 12 as the only product able to be isolated. The failure of unsaturated imine 12 to undergo cyclization may indicate that plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The diphenylbenzazepine unsubstituted at nitrogen, namely, 2,4-diphenyl-1 H -1-benzazepine ( 2d ), would have been ideal to complete the series of benzazepines, including 2a – c . However, this compound is not known and not obtainable by either of our methods for benzazepine synthesis. , We have found that this N-unsubstituted benzazepine is much less thermodynamically stable than its 3 H -isomer 1 and is therefore not detected in the reaction mixture containing 1 . So the N-unsubstituted 2d remained a compound for computations only, and for experimental work, we used diester 4 to complete the series of 1 H -benzazepines, bearing in mind that the carboalkoxy groups of 4 could cause unexpected changes in properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diphenylbenzazepine unsubstituted at nitrogen, namely, 2,4-diphenyl-1 H -1-benzazepine ( 2d ), would have been ideal to complete the series of benzazepines, including 2a – c . However, this compound is not known and not obtainable by either of our methods for benzazepine synthesis. , We have found that this N-unsubstituted benzazepine is much less thermodynamically stable than its 3 H -isomer 1 and is therefore not detected in the reaction mixture containing 1 . So the N-unsubstituted 2d remained a compound for computations only, and for experimental work, we used diester 4 to complete the series of 1 H -benzazepines, bearing in mind that the carboalkoxy groups of 4 could cause unexpected changes in properties.…”
Section: Resultsmentioning
confidence: 99%
“…However, this compound is not known and not obtainable by either of our methods for benzazepine synthesis. 3,30 We have found that this N-unsubstituted benzazepine is much less thermodynamically stable than its 3H-isomer 1 and is therefore not detected in the reaction mixture containing 1. 3 So the N-unsubstituted 2d remained a compound for computations only, and for experimental work, we used diester 4 to complete the series of 1H-benzazepines, bearing in mind that the carboalkoxy groups of 4 could cause unexpected changes in properties.…”
Section: ■ Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Seven benzazepines were chosen for the NMR study (Table ). Benzazepines 2a , 2b , 2c , and 2d are known compounds, and were obtained by literature procedures. The (5-methyl-2-furyl)-substituted benzazepine 2e was prepared by condensation of 2-fluoroaniline with 2-acetyl-5-methylfuran (Scheme ) .…”
Section: Resultsmentioning
confidence: 99%
“…The (5-methyl-2-furyl)-substituted benzazepine 2e was prepared by condensation of 2-fluoroaniline with 2-acetyl-5-methylfuran (Scheme ) . The 4-( o -toluyl)-substituted benzazepine 2f was synthesized in three steps from the trimethylsilyl enol ether of 4′-methylacetophenone ( 4 ), 2′-methylacetophenone, and 2-fluoroaniline (Scheme ). ,, The 3-methyl-substituted benzazepine 2g was prepared by deprotonation of benzazepine 2a with LDA, followed by alkylation of the presumed anion with methyl iodide (Scheme ). This procedure was suggested by the work of Streef and van der Plas, who alkylated 3 H -azepines at C3 in a similar fashion .…”
Section: Resultsmentioning
confidence: 99%